2010
DOI: 10.1007/s10961-010-9186-3
|View full text |Cite
|
Sign up to set email alerts
|

Universities and the success of entrepreneurial ventures: evidence from the small business innovation research program

Abstract: There has been little direct, systematic empirical analysis of the role that universities play in enhancing the success of entrepreneurial ventures. We attempt to fill this gap by analyzing data from the US SBIR program, a ''set-aside'' program that requires key federal agencies (e.g., Department of Defense) to allocate 2.5% of their research budget to small firms that attempt to commercialize new technologies. Based on estimation of Tobit and negative binomial regressions of the determinants of commercial suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(23 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Evidence suggests that although training during the PhD and post-doctoral stages of careers can play an important role in stimulating interest in commercialization and entrepreneurial behavior, a sustained training and support activity such as mentoring by those with commercial experience is required over time to sustain entrepreneurial activities. In a similar vein, this could be mutually beneficial, as studies show that start-ups with close university ties outperform those that do not have such close relationships (Siegel and Wessner 2010).…”
Section: Entrepreneurial Mobilitymentioning
confidence: 99%
“…Evidence suggests that although training during the PhD and post-doctoral stages of careers can play an important role in stimulating interest in commercialization and entrepreneurial behavior, a sustained training and support activity such as mentoring by those with commercial experience is required over time to sustain entrepreneurial activities. In a similar vein, this could be mutually beneficial, as studies show that start-ups with close university ties outperform those that do not have such close relationships (Siegel and Wessner 2010).…”
Section: Entrepreneurial Mobilitymentioning
confidence: 99%
“…Some cases of successes or failures of commercialization previously examined focused on the initial sales of products or services embedded in the transferred technology (Mitchell and Singh, 1996;Nerkar and Shane, 2007), while others considered success as the achievement of specific milestones, such as when new employees are hired or when licensing agreements are consummated (Siegel and Wessner, 2012). In this study, we concentrate on whether the firm had launched its product or service into the market.…”
Section: Research Settingmentioning
confidence: 99%
“…Lerner (2000) found that SBIR awardees were more likely to increase jobs and revenues and to obtain funding from Angels and venture capitalists than non-SBIR awardees were. In addition to Lerner (2000), other studies such as Audretsch, Weigand and Weigand (2002), Audretsch (2003), Huang, Lee and Chu (2004), Link and Scott (2009), Link and Scott (2010), and Siegel and Wessner (2012) explored the role of the SBIR program from the macro perspective of globalization and knowledge economy as well as the functional perspective of public-private partnership and innovation-related risk sharing.…”
Section: A31 Overview Of Sbir Program Assessmentmentioning
confidence: 99%